Monetary policy uncertainty and inflation expectations - Gabriel Arce-Alfaro; Boris Blagov (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
Do inflation expectations react to changes in the volatility of monetary policy? Yes, but only until the global financial crisis. This paper investigates whether increasing the dispersion of monetary policy shocks, which is interpreted as elevated uncertainty surrounding monetary policy, affects the inflation expectation formation process. Based on U.S. data since the 1980s and a stochastic volatility-in-mean structural VAR model we find that monetary policy uncertainty reduces both inflation expectations and inflation. However, after the Great Recession this link has disappeared, even when controlling for the Zero Lower Bound. – – Reagieren die Inflationserwartungen auf Veränderungen der geldpolitischen Volatilität? Ja, allerdings nur bis zur globalen Finanzkrise. In diesem Beitrag wird untersucht, ob eine zunehmende Dispersion geldpolitischer Schocks, die als erhöhte Unsicherheit über die Geldpolitik interpretiert wird, den Prozess der Inflationserwartungsbildung beeinflusst. Basierend auf US-Daten seit den 1980er Jahren und einem strukturellen VAR Modell mit stochastischer Volatilität finden wir, dass geldpolitische Unsicherheit sowohl die Inflationserwartungen als auch die Inflation reduziert. Nach der Großen Rezession ist dieser Zusammenhang jedoch verschwunden, selbst wenn man für die Null-Prozent-Untergrenze der nominalen Zinssätze kontrolliert.
Keywords: C11; C32; E52; 330; Monetary policy uncertainty; inflation expectations; SVAR volatility-in-mean; time-varying coefficients